W.M.L. de Wette's Contributions to Biblical Theology - Reicke, B. (1983)
Wilhelm Martin Leberecht de Wette lived in Germany and Switzerland from 1780 to 1849. He belonged to a family that had emigrated from the Netherlands to Germany in 1559, and several of his ancestors including his father had been Lutheran ministers in the Duchy of Weimar. After six years of study in Jena, he taught theology in Jena, Heidelberg, Berlin, and eventually in Basel from 1822 to his death in 1849.